2015
DOI: 10.1111/apt.13326
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome changes associated with sustained eradication of Clostridium difficile after single faecal microbiota transplantation in children with and without inflammatory bowel disease

Abstract: Summary Background Little data are available regarding the effectiveness and associated microbiome changes of faecal microbiota transplantation (FMT) for Clostridium difficile infection (CDI) in children, especially in those with inflammatory bowel disease (IBD) with presumed underlying dysbiosis. Aim To investigate C. difficile eradication and microbiome changes with FMT in children with and without IBD. Methods Children with a history of recurrent CDI (≥3 recurrences) underwent FMT via colonoscopy. Stool sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 60 publications
2
47
0
Order By: Relevance
“…To investigate the eradication of C. difficile and changes in the microbiome following FMT in children with and without IBD, 8 children (5 with IBD and 3 without IBD) with a history of recurrent CDI (≥3 recurrences) received FMT via colonoscopy. All 8 children showed the resolution of CDI symptoms and eradication of C. difficile at 10–20 weeks and 6 months after the administration of FMT [41]. There was also an increase in the intestinal microbial diversity after FMT therapy [41].…”
Section: Attempt To Restore Normal Diversity To Alleviate Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the eradication of C. difficile and changes in the microbiome following FMT in children with and without IBD, 8 children (5 with IBD and 3 without IBD) with a history of recurrent CDI (≥3 recurrences) received FMT via colonoscopy. All 8 children showed the resolution of CDI symptoms and eradication of C. difficile at 10–20 weeks and 6 months after the administration of FMT [41]. There was also an increase in the intestinal microbial diversity after FMT therapy [41].…”
Section: Attempt To Restore Normal Diversity To Alleviate Ibdmentioning
confidence: 99%
“…All 8 children showed the resolution of CDI symptoms and eradication of C. difficile at 10–20 weeks and 6 months after the administration of FMT [41]. There was also an increase in the intestinal microbial diversity after FMT therapy [41]. Three systematic reviews and a meta-analysis on CDI treated with FMT showed an average curative rate of approximately 90% [4244].…”
Section: Attempt To Restore Normal Diversity To Alleviate Ibdmentioning
confidence: 99%
“…Both durable transmission and clearance of procarcinogenic bacteria occurred following FMT, suggesting that additional studies on appropriate screening measures for FMT donors and the long-term consequences and/or benefits of FMT are warranted. cohorts, including a multicenter cohort of 335 children (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Given its successes in rCDI, FMT is being increasingly explored as a therapeutic option for a number of gastrointestinal disorders, as well as other conditions associated with microbial dysbiosis, with recent promising results in clinical trials in ulcerative colitis (UC) (17)(18)(19) and immune checkpoint inhibitor-associated colitis in cancer patients (20).…”
Section: Resultsmentioning
confidence: 99%
“…This is partly due to the significantly lower incidence of C. difficile colitis in the pediatric age group[21]. However, small case series have shown similar treatment success of FMT in pediatric RCDI as adults, with rates of remission between 89%-100% in children[22] (Table 2). …”
Section: Fmt For the Treatment Of Recurrent Clostridium Difficile Infmentioning
confidence: 99%
“…At 6 mo post FMT, microbiota profiles of patients with IBD returned closer to their pre-FMT baseline composition while those patients without IBD retained similarity to FMT donor stool. This suggests the IBD microbiome may involve a dysbiosis that is more resistant to change than the microbiome of an otherwise healthy individual[22]. …”
Section: Challenges and Opportunities Of Fmtmentioning
confidence: 99%